ЗА НАЗИВИТЕ НА ПТИЦИТЕ ОД РЕДОТ STRIGIFORMES (БУВ, УТ, УТКА, КУКУМЈАВКА), НИВНОТО ЗНАЧЕЊЕ И НАРОДНАТА СИМБОЛИКА ВО МАКЕДОНИЈА - Goce Cvetanovski (Philological Studies, 2019)
In the Macedonian language territory there are many names for birds of the order of Strigiformes (bu, buf, buv, buh, buval, buhal, b'uhƒl, b'uh‚l, buhel, buarec, buo, b'uho, b'uhalo, bulut, bul'utin, b'ula~; ut, utka, 'utalen; lul'ejka, ulejka; d'umo; }or'opile; lo{o pile; ut, 'utalen, 'utka, f'utka, 'utica, 'utajka; kukum'avka, kukumj'afka, kukuq'avka, kukumwavka, kukum'’fk‚ kuk™mj'afka, kukuvejka, kukuvajka, kukuv'e£ka, kukumajka, kukumja~ka, kukuv'aja; k'ukale; url'ejka, urul'ejka, ulumajka, ulejka, ulul'ejka, ulýul'e}a, ul'e}a, uluvejka, uqajka, ulýajka, huluv'ajka, lýulýajka; buf; ~uetarka, ~ovetarka, ~uv'i~ka; pust'ulýka; }u{'e). We try to give an overview of the names of the birds of the order Strigiformes, but will focus on etymology and meaning of the names, beliefs and the symbolism of these birds that exist in the Macedonian folk tradition.